EFEKTIFITAS PROGRAM PEMBIAYAAN PAKET MASA DEPAN DI BTPN SYARIAH DALAM MEMBERDAYAKAN PEREMPUAN UNTUK MENGEMBANGKAN EKONOMI KELUARGA - AINUL IKHSAN; RAHMANI TIMORITA YULIANTI (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The theme of the research is: economics based on Islamic economics. The purpose of this study is to describe and analyze the effectiveness of financing products "Paket Masa Depan" at BTPN Syariah, in empowering women to develop the family economy. Research is qualitative. The research approach used is descriptive approach. Data collection techniques used are through observation, interview and documentation. The results of the research are: Future package financing products in BTPN Syariah Sleman branch office has empowered women.